Stunting Cases In Muaro Jambi District 2019–2021: Spatial Autocorrelation - Sri Astuti Siregar; Muhammad Syukri; Asparian, Asparian; Lia Nurdini (International Journal of Health Engineering and Technology, 2024)
Stunting is a major threat to the quality of Indonesian society. Stunting or short stature is a condition in which children have less height compared to their age. The 2020 Asian Development Bank report, Indonesia is the second highest country in the Southeast Asia region with a stunting prevalence of 31.8%. Children with stunting conditions will be at risk of having a level of intelligence that is not optimal and becomes more susceptible to disease. The impact of stunting is not only experienced by children but can affect in the future to adulthood, this can result in decreased levels of productivity. This study aims to determine the spatial pattern of the distribution of stunting cases in the Muaro Jambi Regency in 2019 – 2021. The research method uses an ecological study design with a spatial approach. The sample in this study used aggregate data of 22 working areas of the Community Health Centers in Muaro Jambi Regency. There is a trend of increasing stunting cases in Muaro Jambi Regency in 2019-2021 with a distribution pattern that is in the form of clusters or clusters and globally shows that there is a positive autocorrelation with the 2 working areas of the Puskesmas, which is calledhot spot area as well as being a priority in tackling stunting cases.